The Influences of compensation, Workload and Work Satisfaction on Employee Performance - Farida Laksitarini (Dinasti Publisher, 2023)
Prior and related research is very important in academic papers and research. Previous or related studies help strengthen theories and phenomena regarding relationships or influences between variables. This article examines the impact of compensation, workload, and work satisfaction on employee performance. Literature survey on human resource management. The purpose of writing this article is to develop hypotheses about effects between variables for use in further research. Here are the results from this research library: 1) Compensation factors influence employee performance; 2) Workload factors affect employee performance; 3) work Satisfaction Factors Affect Employee Performance .